The clinical characteristics and vaccination status of pertussis cases in Jiangning district, Nanjing city from January to May 2024: a surveillance data analysis - Yijun WANG; Tao TAO; Mengqi LI; Yan XU; Jianjun DAI (Zhongguo gonggong weisheng, 2025)
ObjectiveTo analyze the clinical characteristics and pertussis-containing vaccine (PCV) vaccination status of 650 pertussis cases in Jiangning district, Nanjing city, Jiangsu province, to provide a reference for the development of pertussis vaccination and immunization strategies. MethodsData on 650 pertussis cases reported from Jiangning district, Nanjing city, in the China Information System for Disease Control and Prevention from January to May 2024, were collected from the Jiangsu Provincial Integrated Vaccination Service Management Information System. The clinical characteristics and PCV vaccination status of pertussis cases in this area were analyzed. ResultsAmong the 650 pertussis cases in Jiangning district, 640 (98.46%) had a cough, 233 (35.84%) had paroxysmal spasmodic cough, 99 (15.23%) had fever, 81 (12.46%) had vomiting, 61 (9.38%) had pneumonia, and 38 (5.85%) had inspiratory stridor. Comparison of clinical symptoms of pertussis cases in different age groups in Jiangning district showed differences in the incidence of paroxysmal spasmodic cough, vomiting, and pneumonia (all P < 0.05). The incidence of cough (100.00%), paroxysmal spasmodic cough (61.54%), vomiting (30.77%), pneumonia (23.08%), and inspiratory stridor (23.08%) was highest in cases < 3 months of age. Among the cases, 604 (92.92%) had received PCV. The PCV vaccination rates for the < 3 months, 3 months to 2 years, 3 to 5 years, 6 to 11 years, and ≥ 12 years age groups were 0, 86.96%, 95.24%, 98.93%, and 82.05%, respectively. Comparison of pertussis cases in different age groups showed significant differences in vaccination rates (χ2 = 111.63, P < 0.001). The PCV vaccination rate among hospitalized pertussis cases (84.61%) was significantly lower than that among non-hospitalized cases (93.84%) (χ2 = 13.72, P < 0.001). ConclusionsThe incidence of clinical symptoms such as cough, paroxysmal spasmodic cough, vomiting, pneumonia, and inspiratory stridor was higher in pertussis cases < 3 months of age in Jiangning district, and none of these cases had received PCV. The vaccination rate was higher among non-hospitalized cases.